2016
DOI: 10.1016/s0140-6736(15)00238-x
|View full text |Cite
|
Sign up to set email alerts
|

Attention deficit hyperactivity disorder

Abstract: The causes of ADHD are complex and multifactorial, with genetics, early environment and gene-environment interplay all being involved. No single risk factor is either necessary or sufficient to explain its occurrence. ADHD is highly heritable, and multiple types of genetic variants appear to be involved. None are diagnostic. Early environmental factors (e.g. diet, pre-and perinatal factors, toxins and psychosocial risks) have also been extensively investigated but whilst correlations have been found between ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
638
5
43

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 820 publications
(704 citation statements)
references
References 121 publications
18
638
5
43
Order By: Relevance
“…This might have indicated that a few risk factors for ADHD such as environmental exposure, complications of pregnancy and delivery and psychosocial adversity may vary in different settings (Benjasuwantep, Ruangdaraganon, & Visudhiphan, 2002). Most studies found that ADHD was more common among males (Thapar & Cooper, 2016). In the present study, the prevalence of ADHD among boys tended to be higher but not statistically significant, which could have been due to the small sample size.…”
Section: Discussioncontrasting
confidence: 86%
“…This might have indicated that a few risk factors for ADHD such as environmental exposure, complications of pregnancy and delivery and psychosocial adversity may vary in different settings (Benjasuwantep, Ruangdaraganon, & Visudhiphan, 2002). Most studies found that ADHD was more common among males (Thapar & Cooper, 2016). In the present study, the prevalence of ADHD among boys tended to be higher but not statistically significant, which could have been due to the small sample size.…”
Section: Discussioncontrasting
confidence: 86%
“…Although this figure is lower than the rate of comorbid ADHD (80%) previously reported in a clinic specializing in FM [7], it is similar to the figure of 25% reported in patients with FM by Derksen et al [8]. A recent meta-analysis estimated that the global prevalence of adult ADHD was 2.5% [20], while it has been estimated to be 1.7% in Japan [21]. The rate in the current study was 12.7 times that of the estimated global rate, and 19.3 times that of the estimated rate in Japan.…”
Section: Discussionsupporting
confidence: 77%
“…Third, our use of a screening instrument for defining the groups will have resulted in different exclusions to those using diagnostic instruments, which has been raised as a limitation of this type of research (Caye et al., 2017). However, given that ADHD symptoms act as a continuously distributed dimension in terms of associations with risk factors and outcomes (Thapar & Cooper, 2016) and our ADHD measure at age 17 years remained based on the same informant at all time points (parent report) as opposed to switching from parent to self‐report our investigation has many strengths as well as limitations. Nevertheless, assessment issues aside, we do still identify a group of those with late‐onset ADHD in keeping with a previous report using a less stringent cut‐point in this same data set (Riglin et al., 2016) as well as other studies (Agnew‐Blais et al., 2016; Caye et al., 2016; Moffitt et al., 2015; Sibley, Rohde et al., 2017).…”
Section: Discussionmentioning
confidence: 99%